Research progress of Traditional Chinese Medicine five-element music therapy (中医五行音乐疗法的研究进展) - LI Suqian (李苏茜); LU Lin (芦琳); TANG Ling (唐玲); WANG Chun (王纯) (中西医结合护理)
Based on the theory of Traditional Chinese medicine, the five-element music therapy uses the ancient Chinese five-tone scale, including Gong(do), Shang(rei), Jiao(mi), Zi(sou) and Yu(la), to regulate the five internal organs, so as to regulate Qi and blood, relieve emotional and mental stress and eliminate diseases. At present, five-element music has been widely used, which can play a good effect on pain, anxiety, insomnia and other symptoms. This paper summarized the clinical application of Traditional Chinese Medicine five-element music, in order to provide reference for the further research and clinical practice. (中医五行音乐疗法以中医学理论为基础, 运用“宫、商、角、徵、羽”五个声阶来调节五脏从而调和气血、调节情志以养生祛病。五行音乐疗法在临床应用广泛, 在减轻疼痛、缓解焦虑、改善失眠等方面均取得了良好效果。本文就中医五行音乐疗法临床应用进行总结, 以期为该疗法的进一步研究提供参考。)